Pengembangan Media Berbasis Articulate Storyline 3 Pada Pembelajaran Tematik Terpadu di Kelas V Sekolah Dasar - Monalisa, Agnes; Ariani, Yetti (Universitas Negeri Padang, 2024)
This research is motivated by the fact that there is a lack of innovation in learning media that uses technology. The learning media that tends to be used is learning media in the form of teaching aids that exist in the environment of students such as used goods. This research aims to develop learning media based on Articulate Storyline 3 in integrated thematic learning for grade V in elementary schools that are valid and practical to be applied to the learning process. The type of research used is development research (R&D) with the ADDIE model which consists of five stages, namely analysis, design, development, implementation, and evaluation. Data from this study were obtained from validation sheets and response questionnaires. The validation sheet consists of material, language, and media expert validation. Meanwhile, the response questionnaire consists of teacher and learner response questionnaires. The test subjects of this research were 26 students consisting of 16 male students and 10 female students in class VA SDN 01 Bandar Buat. The results of this study as a whole obtained a final validation result of 94% with the category